GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 6147 species occurrences available in GBIF matching the query: TaxonKey: Trogon mexicanus Swainson, 1827 HasCoordinate: true HasGeospatialIssue: false. The dataset includes 6147 records from 43 constituent datasets: 4 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 239 records from Avifauna de la Reserva de la Mariposa Monarca. 1 records from DMNS Bird Collection (Arctos). 61 records from Museum of Comparative Zoology, Harvard University. 28 records from CAS Ornithology (ORN). 4154 records from EOD - eBird Observation Dataset. 20 records from iNaturalist Research-grade Observations. 2 records from Aves de México I. 7 records from LACM Vertebrate Collection. 2 records from Digitalización de la Biblioteca de Sonidos Naturales del Museo de Zoología, Facultad de Ciencias, UNAM. 22 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 11 records from Macaulay Library Audio and Video Collection. 82 records from Base de datos de aves mexicanas del Natural History Museum, Tring, Inglaterra. 25 records from Distribución geográfica de las aves y los mamíferos del estado de Querétaro. 18 records from Distribución geográfica de las aves y los mamíferos de las zonas montanas de los estados de San Luis Potosí e Hidalgo circundantes de la Sierra Gorda. 18 records from Sistematización de las colecciones científicas del Instituto de Historia Natural y Ecología, (IHNE) Chiapas. 17 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 2 records from Aves de las reservas de la biosfera de Durango: La Michilía y Mapimí. 135 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 262 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 20 records from Obtención de la riqueza de aves y selección de especies susceptibles de monitoreo en la zona noroeste en el estado de Chiapas. 1 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 8 records from Avifauna de la reserva de la biosfera El Cielo, Tamaulipas, México. 20 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 2 records from RBINS DaRWIN. 1 records from UWBM Ornithology Collection. 21 records from CNAV/Coleccion Nacional de Aves. 27 records from Colección Ornitológica del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 39 records from MZFC/Coleccion de Aves. 32 records from WFVZ Bird Collections. 102 records from MLZ Bird Collection (Arctos). 18 records from AMNH Bird Collection. 1 records from MVZ Egg and Nest Collection (Arctos). 79 records from Bosque Mesófilo de Montaña de México. 3 records from CM Birds Collection. 1 records from Vocalizaciones de aves mexicanas en análisis biogeográficos y reconstrucción filogenética. 7 records from Biodiversidad, hábitat y manejo en el Parque Nacional Pico de Tancítaro, Michoacán, México. 18 records from UMMZ Birds Collection. 45 records from DMNH Birds. 40 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 44 records from MVZ Bird Collection (Arctos). 3 records from KUBI Ornithology Collection. 505 records from Atlas de las Aves de México: Fase II. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences